2012
DOI: 10.2174/156652412800163415
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Evolution of the Translocator Protein (18 kDa)

Abstract: Translocator proteins (TSPO) are the products of a family of genes that is evolutionarily conserved from bacteria to humans and expressed in most mammalian tissues and cells. Human TSPO (18 kDa) is expressed at high levels in steroid synthesizing endocrine tissues where it localizes to mitochondria and functions in the first step of steroid formation, the transport of cholesterol into the mitochondria. TSPO expression is elevated in cancerous tissues and during tissue injury, which has lead to the hypothesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 117 publications
(175 reference statements)
0
11
0
1
Order By: Relevance
“…On the basis of these studies, we conclude that liver mitochondria lacking TSPO function essentially as do control mitochondria. Whether proposed functions of TSPO in cholesterol and heme transport and in steroidogenesis (1)(2)(3)(4)(5)(6) are compensated by mechanisms that we have not addressed here remains to be established. Indeed, recent similar genetic studies have called into question the precise role of TSPO in steroid hormone biogenesis (7).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…On the basis of these studies, we conclude that liver mitochondria lacking TSPO function essentially as do control mitochondria. Whether proposed functions of TSPO in cholesterol and heme transport and in steroidogenesis (1)(2)(3)(4)(5)(6) are compensated by mechanisms that we have not addressed here remains to be established. Indeed, recent similar genetic studies have called into question the precise role of TSPO in steroid hormone biogenesis (7).…”
Section: Discussionmentioning
confidence: 96%
“…TSPO Is Not Required for Porphyrin-mediated Photodynamic Effects on the PTP-We have previously reported that in isolated mitochondria, the PT can be modulated by photooxidative stress following UV-visible light irradiation of PP IX-like dicarboxylic porphyrins associated with mitochondria, resulting in the production of reactive oxygen species (primarily singlet oxygen, 1 O 2 ) (65). Earlier studies have demonstrated that such photooxidative stress promotes modification of vicinal targets at two critical sites.…”
Section: Tspo Does Not Play a Role In The Regulation Of Pt-mentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian TSPO/PBR is homologues to bacterial TspO proteins, which have a high content of tryptophan residues [39]. Accordingly, several tryptophan residues of mTSPO/PBR are conserved such as Trp 33 Topological analysis has suggested that the flexible Cterminus, the TM3-TM4 loop and the TM1-TM2 loop are located on the extra-mitochondrial side [25].…”
Section: D Structure Of Mammalian Tspo/pbr In Complex With Pk11195mentioning
confidence: 99%
“…En mamíferos, la significancia biológica de la TSPO ha sido estudiada por décadas y ha sido relacionada con múltiples funciones celulares, siendo la regulación del transporte de colesterol a través de las membranas mitocondriales, la función mejor caracterizada (33).…”
Section: Proteína Translocadora Mitocondrial (Tspo) 18 Kdaunclassified